DravidianCodeMix: sentiment analysis and offensive language identification dataset for Dravidian languages in code-mixed text - Chakravarthi, Bharathi Raja; Priyadharshini, Ruba; Muralidaran, Vigneshwaran; Jose, Navya; Suryawanshi, Shardul; Sherly, Elizabeth; McCrae, John P. (Language resources and evaluation, 2022)
This paper describes the development of a multilingual, manually annotated dataset for three under-resourced Dravidian languages generated from social media comments. The dataset was annotated for sentiment analysis and offensive language identification for a total of more than 60,000 YouTube comments. The dataset consists of around 44,000 comments in Tamil-English, around 7000 comments in Kannada-English, and around 20,000 comments in Malayalam-English. The data was manually annotated by volunteer annotators and has a high inter-annotator agreement in Krippendorff’s alpha. The dataset contains all types of code-mixing phenomena since it comprises user-generated content from a multilingual country. We also present baseline experiments to establish benchmarks on the dataset using machine learning and deep learning methods. The dataset is available on Github and Zenodo.